2020
DOI: 10.34172/jrip.2020.19
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 interactions with angiotensin-converting enzyme 2 (ACE2) and the kinin system; looking at a potential treatment

Abstract: The novel coronavirus disease 2019 (COVID-19) is a rapidly expanding infection around the world. The world Health Organization (WHO) in March 2020 announced the Coronavirus pandemic. This infection causes many deaths on daily basis. Therapeutic options are currently limited. It is revealed that COVID-19 binds to human angiotensin-converting enzyme 2 (ACE2) to enter the host cells. One of the activities of ACE2 is hydrolyzing the active bradykinin metabolite [des-Arg973] BK (DABK). A decreased activity or reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 24 publications
2
83
0
6
Order By: Relevance
“…But more studies regarding BK-mediated urticaria are needed. [8][9][10] Letters to the Editor Apparently, previous studies showed there was not any correlation of urticaria in COVID-19 with disease's severity, which is consistent with our case, because the patient was in stable condition and to date has fully recovered.…”
Section: Dear Editorsupporting
confidence: 88%
“…But more studies regarding BK-mediated urticaria are needed. [8][9][10] Letters to the Editor Apparently, previous studies showed there was not any correlation of urticaria in COVID-19 with disease's severity, which is consistent with our case, because the patient was in stable condition and to date has fully recovered.…”
Section: Dear Editorsupporting
confidence: 88%
“…ACE-2 KO mice exhibit severe pathology of ARDS and age-related loss of ACE-2 in the lungs correlates with increased mortality and worsened phenotype in elderly patients with COVID-19 [60,64]. Exogenous administration of ACE-2 in patients with ARDS did not show any difference in oxygenation index or clinical outcomes, although there was a trend of decreasing IL-6 concentrations [65]. A recent study showed that upregulation of ZEB1 reduced ACE-2 expression, which in turn downregulated claudins, thus, increasing risk and pathogenesis of edema and ARDS in COVID-19 patients [66].…”
Section: Role Of Ace-2 and Tmprss2 In Lung Disease/covid-19mentioning
confidence: 86%
“…Following viral binding, ACE2 expression and activity is eventually downregulated by the virus through multiple mechanisms, preventing it from performing its usual function in states of health (40). The downregulation of ACE2 signaling induces the kallikrein-kinin system which is activated during in ammatory conditions with vascular-alveolar uid extravasation, leukocyte extravasation and recruitment to the lung and acute respiratory distress syndrome (ARDS), lung injury and pneumonia (41).…”
Section: Other Ace2-related Mechanismsmentioning
confidence: 99%